Synthesis of PbO Nano-Particles From a New One-Dimensional Lead(II) Coordination Polymer Precursor - Sadeghzadeh, H.; Morsali, A.; Yilmaz, V.T.; Büyuk̈güngör, O. (Elsevier Science BV, 2010)
A new Pb(II) one-dimensional coordination polymer, [Pb(μ-NO2)(μ-pyc)(H2O)]n (1), Hpyc = 2-pyridinecarboxylic acid} was prepared and characterized by elemental analyses, powder XRD diffraction and IR spectroscopy. Compound 1 was structurally characterized by single-crystal X-ray diffraction and one-dimensional coordination polymer with coordination environment of PbNO6. The thermal stability of compound 1 showed that compound 1 decomposes at 110-500 °C and the final product is PbO. This polymeric precursor has been used to make PbO nano-particles using two different surfactants. The new nano-structure was characterized by scanning electron microscopy and X-ray powder diffraction. This study demonstrates that the coordination polymers may be suitable precursors for the preparation of nanoscale materials. © 2010 Elsevier B.V. All rights reserved.
Keywords: Crystal Structure; Nano-Materials; Thermal Properties